Konseptualisasi Konstruksi Kurikulum Kelas Khusus Olahraga Berbasis Kecerdasan Kinestetik dan Adversity Quotient di SMA: Perspektif Islam Berkemajuan - Eko Mulyadi; Mhd. Lailan Arqam; Ishafit Ishafit; Hendro Widodo (Balai Teknologi dan Komunikasi Pendidikan DIY, 2026)
The Special Sports Class (SSC) program in high schools still faces various obstacles, especially because there is no curriculum specifically designed to balance sports achievements, academic achievement, and character development of students. This research aims to formulate the concept of the KKO curriculum that focuses on kinesthetic intelligence and Adversity Quotient (AQ) in the framework of Muhammadiyah Progressive Islam. The method used in this study is a qualitative approach with case study design in several locations, namely at SMAN 1 Sewon Bantul, MAN 2 Yogyakarta, and SMAS Muhammadiyah 7 Yogyakarta. Data collection was carried out through in-depth interviews, targeted participatory observations, and documentation studies, followed by data analysis using the Yin interactive model which included data organization, coding, case analysis, case-to-case analysis, and pattern matching techniques. The findings of the study show that the KKO curriculum still follows the general curriculum, so it has not been able to integrate the development of kinesthetic intelligence, mental resilience, and Progressive Islamic values systematically. This research resulted in a KK-AQ Integrative Curriculum model that is built on three main pillars, namely the flexibility of the curriculum structure, differentiated learning that focuses on sports activities, and the habituation of Adversity Quotient. This model is integrated with the values of Progressive Islam, including tajdid, tauhid, rahmatan lil 'alamin, ijtihad, and wasathiyah, so as to be able to form students who excel in sports, academics, character, and spirituality in a balanced manner